Hoberman's Sphere as a Visual of Social Structure - Krieg, Andrea (TRAILS: Teaching Resources and Innovations Library for Sociology, 2021)
Instructors, the ASA, and other sociological leaders agree that social structure is an essential concept to a sociology curriculum (e.g. ASA 2004; Persell, Pfeiffer, and Syed 2007; Grauerholz and Gibson 2006; Wagenaar 1991) . After examining the pedagogical research, as well as popular introductory textbooks, it is clear that although we espouse its importance, we often leave students with a vague understanding of what we really mean. I certainly agree with Manza (2017) when he states that it would take an entire semester to sufficiently teach the topic, and I understand that instructors already have a significant amount to cover in a limited amount of time. Therefore, I offer an innovative pedagogical tool that can be used to help students visualize what we mean by social structure.